Modifikasi sistem pressure pada Air Brake Roll Treatment Let off Bias cutting menggunakan Sensor Distance IFM O1D100 - Firdausi, Muhamad Kahlil; Widiantoro, Rahmat; Rusydi, Muhammad Ibnu; Susilawati, Dera (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
At PT XYZ, the Bias cutting process plays a crucial role in tire production, particularly in the handling ofTreatment rolls involving the Air Brake Roll Treatment system. Currently, pressure adjustment on the Bias cutting machine at the Let Off section is performed manually by operators, often leading to inaccuracies in pressure reduction. These inaccuracies result in uneven compression of the Treatment rolls, leading to increased scrap rates and reduced production efficiency. This study aims to modify the pressure system by replacing the manual method with an automated system using the IFM O1D100 Distance Sensor. This modification involves automatically adjusting pressure based on the distance of the Treatment roll, thereby reducing the risk of unwanted compression and enhancing the consistency of the Bias cutting process. The study results show that using an electro-pneumatic system controlled by the Distance Sensor allows for more precise pressure adjustment, contributing to reduced scrap rates and improved production efficiency.